2019
DOI: 10.3168/jds.2019-16615
|View full text |Cite
|
Sign up to set email alerts
|

Production of cheese from donkey milk as influenced by addition of transglutaminase

Abstract: Donkey milk is characterized by low contents of total solids, fat, and caseins, especially κ-casein, which results in formation of a very weak gel upon renneting. The objective of this study was to evaluate the effect of fortification of donkey milk with microbial transglutaminase (MTGase) for cheesemaking in relation to different enzyme addition protocols (patterns, PAT). Four independent trials were performed using MTGase (5.0 U/g of milk protein) according to the following experimental patterns: control (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
0
18
0
1
Order By: Relevance
“…Therefore, a timely treatment of the raw sample would be recommended to avoid the proliferation of an unwanted microflora, which could irreparably compromise the use of donkey milk for human consumption, and for any technological transformations. Also, in light of suggested cheese production from donkey raw milk [21,55], our findings suggested precautions to be adopted to assure the quality and the safety of these dairy products, including the possible risks associated with spontaneous fermentation [56,57].…”
Section: Analysis Of Bacterial Diversitymentioning
confidence: 89%
“…Therefore, a timely treatment of the raw sample would be recommended to avoid the proliferation of an unwanted microflora, which could irreparably compromise the use of donkey milk for human consumption, and for any technological transformations. Also, in light of suggested cheese production from donkey raw milk [21,55], our findings suggested precautions to be adopted to assure the quality and the safety of these dairy products, including the possible risks associated with spontaneous fermentation [56,57].…”
Section: Analysis Of Bacterial Diversitymentioning
confidence: 89%
“…MTGase is known to lead to the formation of a network among proteins and high molecular weight peptides, modifying the products’ protein functional properties and rheological characteristics. The results showed that the enzyme, when added simultaneously with the rennet to acidified milk (pH 6.3; 42 °C), improved the firmness of the cur, and favored the syneresis process and the retention of milk proteins [ 131 ]. From the data in Table 3 , it can be concluded that different types of rennet can be used for donkey milk cheesemaking, but the curd obtained is always weak and is only suitable for making fresh cheese.…”
Section: Dairy Productsmentioning
confidence: 99%
“…Donkey milk is a basic ingredient for the production of high-value dairy products [89]. DM lysozyme is also used in the food industry due to its stability and resistance to various technological processes such as thermic treatment [31] and digestive tract conditions such as acid pH and gastrointestinal enzymes [90].…”
Section: Food and Other Applications Of Donkey Milkmentioning
confidence: 99%
“…Because of its low fat and casein content, DM constitutes a soft gel during cheese manufacturing. Several studies have faced this situation, for example, by the addition of MTGase-a microbial transglutaminase that can enhance the texture of the curd without any effect on moisture, proteins, fats, or cheese yield [89]. Šarić et al (2016) overcame this limitation by mixing DM with goat milk to produce a functional product with high quality [94].…”
Section: Food and Other Applications Of Donkey Milkmentioning
confidence: 99%